Entry and competition effects in first-price auctions: Theory and evidence from procurement auctions - Tong Li; Xiaoyong Zheng (Centre for Microdata Methods and Practice (cemmap), 2006)
Motivated by several interesting features of the highway mowing auction data from Texas Department of Transportation (TDoT), we propose a two-stage procurement auction model with endogenous entry and uncertain number of actual bidders. Our entry and bidding models pro vide several interesting implications. For the first time, we show that even within an independent private value paradigm, as the number of potential bidders increases, bidders equilibrium bidding behavior may become less aggressive because the entry effect is always positive and may dominate the negative competition effect. We also show that it is possible that the relationship between the expected winning bid and the number of potential bidders is non-monotone decreasing as well. We then develop an empirical model of entry and bidding controlling for unobserved auction heterogeneity to analyze the data. The structural estimates are used to quantify the entry effect and the competition effect with regard to the individual bids and the procurement cost, as well as the savings for the government with regard to the procurement cost when the entry cost is reduced.
Keywords: 330